2009
DOI: 10.1080/00016480902725197
|View full text |Cite
|
Sign up to set email alerts
|

Local application of hepatocyte growth factor using gelatin hydrogels attenuates noise-induced hearing loss in guinea pigs

Abstract: Local HGF treatment significantly reduced the noise exposure-caused ABR threshold shifts and the loss of outer hair cells in the basal portion of the cochleae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 19 publications
2
29
0
Order By: Relevance
“…ABR thresholds at 4, 8, and 16 kHz were recorded before, immediately after surgery, and 3, 7, 14, 21, and 28 days post-operatively (Figure 2). Pretreatment baseline ABR thresholds did not differ among the five groups and were consistent with data previously obtained in our laboratory [15]. Our surgical procedure caused average hearing loss around 61 dB, whereas noncoated, hydrogel-coated, IGF1, HGF, and IGF plus HGF electrodes shifted ABR thresholds by 70 ± 14, 57 ± 11, 52 ± 20, 62 ± 21, and 65 ± 26 dB (mean ± SD), respectively.…”
Section: Alterations In Abr Thresholds After Drug-eluting Electrode Isupporting
confidence: 77%
See 3 more Smart Citations
“…ABR thresholds at 4, 8, and 16 kHz were recorded before, immediately after surgery, and 3, 7, 14, 21, and 28 days post-operatively (Figure 2). Pretreatment baseline ABR thresholds did not differ among the five groups and were consistent with data previously obtained in our laboratory [15]. Our surgical procedure caused average hearing loss around 61 dB, whereas noncoated, hydrogel-coated, IGF1, HGF, and IGF plus HGF electrodes shifted ABR thresholds by 70 ± 14, 57 ± 11, 52 ± 20, 62 ± 21, and 65 ± 26 dB (mean ± SD), respectively.…”
Section: Alterations In Abr Thresholds After Drug-eluting Electrode Isupporting
confidence: 77%
“…We found that local HGF treatment significantly reduced ABR threshold shifts and loss of outer hair cells in the basal portion of damaged cochleae due to noise exposure [15]. HGF activates ectodermal cell outgrowth in a similar pathway as IGF1 [27]; however, since HGF has different molecular weight (69 kDa for α-subunit and 34 kDa for β-subunit) compared to that of IGF1 (7.6 kDa), HGF may abundantly distribute in the basal portion of the cochlea in comparison with the distribution of IGF1.…”
Section: A B D E Cmentioning
confidence: 87%
See 2 more Smart Citations
“…A number of investigators have started to explore their potential use in the middle ear, and findings to date have been encouraging Chen et al, 2006;Kitahara et al, 2008;Paulson et al, 2008;Inaoka et al, 2009]. Here, the potential of poloxamer 407 hydrogels as drug carriers for local delivery of dexamethasone to the inner ear was investigated.…”
mentioning
confidence: 99%